2008
DOI: 10.1038/bjp.2008.356
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits myelin basic protein‐induced human mast cell activation and mast cell‐dependent stimulation of Jurkat T cells

Abstract: Background and purpose: Allergic inflammation and autoimmune diseases, such as atopic dermatitis, psoriasis and multiple sclerosis (MS), involve both mast cell and T‐cell activation. However, possible interactions between the two and the mechanism of such activations are largely unknown. Experimental approach: Human umbilical cord blood‐derived cultured mast cells (hCBMCs) and Jurkat T cells were incubated separately or together, following activation with myelin basic protein (MBP), as well as with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 62 publications
1
82
0
5
Order By: Relevance
“…MCs are the only cell type in which preformed TNF is stored in secretory granules (Olszewski et al, 2007) and released bound to heparin particles that can reach draining lymph nodes and contribute to inflammation (Kunder et al, 2009). TNF can also activate T cells Kempuraj et al, 2008). MC-derived IL-6 and transforming growth factor-b are critical for the development of Th-17 cells Suurmond et al, 2011), and MCs secrete IL-17 themselves (Kenna and Brown, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…MCs are the only cell type in which preformed TNF is stored in secretory granules (Olszewski et al, 2007) and released bound to heparin particles that can reach draining lymph nodes and contribute to inflammation (Kunder et al, 2009). TNF can also activate T cells Kempuraj et al, 2008). MC-derived IL-6 and transforming growth factor-b are critical for the development of Th-17 cells Suurmond et al, 2011), and MCs secrete IL-17 themselves (Kenna and Brown, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-␣ has been described as an immunoprotective factor produced by mast cells to efficiently recruit neutrophils to bacterium-infected tissues (15,20,22,27,35). Previous studies with other bacterial infection models showed that no cells expressing TNF-␣ mRNA were identified in mast cell-deficient Sl /Kitl Sl-d mast cell-deficient mice might offer another explanation for the reduced recruitment of neutrophils in the lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin inhibits mast cells (Kandere-Grzybowska et al, 2006), and also inhibited and reversed acute stress-induced autistic-like behavior and the associated reduced brain glutathione levels in mice (Kumar & Goyal, 2008). Luteolin can also block mast cell activation and superstimulation of activated T-cells (Kempuraj et al, 2008;Theoharides et al, 2007a). Luteolin and its structural analog diosmin prevented MIA-induced behavioral deficits in the mouse offspring by blocking the IL-6-induced JAK2/STAT3 (Janus tyrosine kinase-2/signal transducer and activator of transcription-3) signaling pathway, both in vivo and in vitro (Parker-Athill et al, 2009).…”
Section: Oxidative Stress and Prematuritymentioning
confidence: 98%